Robust ultra wideband time of arrival estimation for indoor localization applications - Xu, Chi (2010)
Ultra wideband (UWB) technology is particularly suitable for localization applications due to its fine time resolution, low power consumption, low complexity receiver design, and low probability of interception. The main goal of this thesis is to provide a good understanding of the challenges posed by UWB time of arrival (TOA) estimation in realistic indoor environments and develop robust TOA estimation techniques. To get insight into how the UWB signal performs in real indoor environments, experiments are carried out to collect a database of received signals captured in various indoor environments including both line-ofsight (LOS) and non-line-of-sight (NLOS) scenarios. With the measurement results, we perform the analysis and answer the following questions: How does the TOA estimation with different types of receivers perform in real indoor environment, what are the effects of system parameter settings on accuracy, and how do the ranging errors behave in real indoor environments? The study shows that the system parameter settings have a heavy impact on the performance especially in LOS environment. The analysis also allows us to build up a unified ranging error model that is applicable for both coherent and energy detection receivers. To improve the accuracy while at the same time retain the low system complexity, we come up with several new techniques. The information of transmitted power combined with certain channel knowledge allows us to devise a delay-dependent threshold setting strategy that helps the estimation overcome the excessive noise. The study also indicates that the threshold setting strategy is insensitive to possible variation or inaccuracy existing in the available power delay profile and small-scale fading channel parameters. To overcome the clutter problem, a novel least square (LS) TOA estimator is developed for UWB backscattering RFID system with tag implementing antipodal 2-Pulse-Amplitude-Modulation(2-PAM). We show that the proposed estimator is inherently immune to the clutter for arbitrary data sequence. The performance of the estimator is evaluated by both simulation and practical measurements. The above solution, however, requires the sampling rate of the order of GHz for UWB signal. To lower down the sampling rate requirement, we propose an RFID system implementing a dual pulse (DP) modulator in the tag which enables the use of the low complexity autocorrelation receiver in the reader. The polarity of modulated signal is jointly determined by a ranging sequence and a pseudorandom noise (PN) sequence. A low complexity two-stage TOA estimator is developed for the proposed system. When ranging sequence, PN sequence and sampling duration are properly selected, part of the clutter terms at the output of the autocorrelation receiver can be completely eliminated while the rest can be reduced by averaging over more symbols. The two solutions have their own advantages. The first one has better clutter suppression capability and does not require dedicated design for data sequence whereas the second one requires receiver with lower complexity and lower sampling rate. The performances of both solutions are validated by simulation results.